2015
DOI: 10.1108/mf-01-2014-0024
|View full text |Cite
|
Sign up to set email alerts
|

Dividend policy in India: new survey evidence

Abstract: Purpose – The purpose of this paper is to survey managers of dividend-paying firms listed on the National Stock Exchange (NSE) in India to learn their views about the factors influencing dividend policy, dividend issues, and explanations for paying cash dividends and repurchasing shares. The authors compare the results to other dividend surveys based on firms in Indonesia, Canada, and the USA. Design/methodology/approach – The authors us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
44
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 47 publications
17
44
2
1
Order By: Relevance
“…In another study, Brav et al (2005) also show support for Lintner's behaviour modelespecially, they indicate that one of Lintner's key findings still holds; managers are reluctant to cut dividends and the current level of dividend payments is taken as given unless adverse circumstances are likely to persist. In addition to above surveys conducted in the U.S., a string of studies providing survey evidence in different countries (from both developed and emerging markets), such as Baker et al (2006) in Norway, Baker et al (2008) in Canada, Baker and Powell (2012) in Indonesia, Baker and Kapoor (2015) in India and Baker et al (2018) in Turkey, have all reported general support for Lintner's partial adjustment model. Mookerjee's (1992) research is one of the earliest studies that quantitatively apply the Lintner model to different developing markets.…”
Section: Studies Of the Partial Adjustment Modelmentioning
confidence: 98%
“…In another study, Brav et al (2005) also show support for Lintner's behaviour modelespecially, they indicate that one of Lintner's key findings still holds; managers are reluctant to cut dividends and the current level of dividend payments is taken as given unless adverse circumstances are likely to persist. In addition to above surveys conducted in the U.S., a string of studies providing survey evidence in different countries (from both developed and emerging markets), such as Baker et al (2006) in Norway, Baker et al (2008) in Canada, Baker and Powell (2012) in Indonesia, Baker and Kapoor (2015) in India and Baker et al (2018) in Turkey, have all reported general support for Lintner's partial adjustment model. Mookerjee's (1992) research is one of the earliest studies that quantitatively apply the Lintner model to different developing markets.…”
Section: Studies Of the Partial Adjustment Modelmentioning
confidence: 98%
“…For instance, Pruitt and Gitman (1991) investigate major firms in the US and report that dividend policy is largely influenced by the current year's earnings. Other studies confirm this relationship in emerging markets such as Turkey (Adaoglu, 2000), India (Baker and Kapoor, 2015), and MENA (Jabbouri, 2016). H1 There is a positive relationship between dividend payout ratio and current profits.…”
Section: Current Profitabilitymentioning
confidence: 75%
“…The study revealed that a situation with the payment of dividends in the corporate sector in Ukraine is quite indistinctive for more developed and emerging stock markets where payment of dividends is not an exclusion [Baker and Kapoor 2015, Forti and Schiozer 2015, Kadioglu et al 2015, Manneh and Naser 2015, Yaseen et al 2015 Is it possible to explain the mass abandonment of dividends payment with the help of modern theories of dividend policy, that were considered in the LITERATURE REVIEW section?.…”
Section: Discussionmentioning
confidence: 99%